Judgmental adjustments through supply integration for strategic partnerships in food chains - Eksoz, Can; Mansouri, S. Afshin; Bourlakis, Michael; Önkal, Dilek (Elsevier, 2018)
Despite significant attention to strategic partnerships among members of supply chains, there has been limited research in food supply chains where such partnerships can provide a competitive advantage through forecasting practices of time-sensitive food items in volatile business environments. The current paper aims to close this gap by examining manufacturers’ strategic partnerships with retailers, with a special emphasis on information sharing, integration, and collaborative forecasting of time-sensitive products in food supply chains. Through Partial Least Square (PLS) analysis of survey data collected from 105 food manufacturers in Europe and North America, this research reveals the importance of strategic partnerships for satisfaction from forecasts generated for perishable, seasonal, promotional and newly-launched products in the food industry. Group forecasting and manufacturers’ external integration with retailers are found to be significant for strategic partnerships. In addition, our findings show that manufacturers’ internal integration is positively associated with group forecasting, external integration and judgmental adjustments. Our findings also reveal that information sharing with retailers facilitates consensus forecasts in group forecasting. These results provide unique insights to researchers and practitioners of human judgment in supply chain forecasting towards enhancing strategic partnerships in food supply chains.
Keywords: Forecast satisfaction; Judgmental adjustments; Strategic partnerships; Supply integration; Food supply chain